Does the functional leaf anatomy of Justicia calycina (Acanthaceae) reflect variation across a canopy gradient in the Southern Brazilian Amazon? - Lauton, Maísa Barbosa; Gressler, Eliana; Oliveira, Jaqueline Amorim de; Simioni, Priscila Fernanda; Gomes Ribeiro-Júnior, Norberto; Yamashita, Oscar Mitsuo; Silva, Ivone Vieira da (Acta Botânica Brasílica, 2022)
ABSTRACT Justicia calycina is a subshrub well distributed in northern South America. Despite its widespread occurrence, little is known about its anatomy and plasticity in different environments. Our study aimed to evaluate how leaf anatomical traits of J. calycina adjust in forest areas with variations in canopy openness in the Southern Amazon, Mato Grosso State, Brazil. Forest areas were: Open and Dense Ombrophilous Forest, and Seasonal Deciduous Forest (rocky outcrop). We performed anatomical measurements in leaves sampled on 10 individuals in each forest site, with the help of usual anatomy techniques. Foliar anatomy of J. calycina showed similar pattern among the studied forests, with significant difference (p<0.05) in four leaf traits among 22 studied: vascular bundle diameter, palisade parenchyma thickness, stomatal density and trichome density in adaxial epidermis. These leaf traits showed high plasticity index, with higher values in Dense Forest and in Deciduous Forest. Even though J. calycina showed overall little anatomical variation among forest types, the few attributes that differed are fundamental in the photosynthesis process. The adjustment in leaf anatomical traits under different luminosity conditions demonstrates a degree of phenotypic plasticity in the species, which contributes to its distribution in different forest phytophysiognomies in Brazilian Amazonia.